On the Role of the Ventromedial Prefrontal Cortex in Self-Processing: The Valuation Hypothesis - D'Argembeau, Arnaud (Frontiers in Human Neuroscience, 2013)
With the development of functional neuroimaging, important progress has been made in identifying the brain regions involved in self-related processing. One of the most consistent findings has been that the ventromedial prefrontal cortex (vMPFC) is activated when people contemplate various aspects of themselves and their life, such their traits, experiences, preferences, abilities, and goals. Recent evidence suggests that this region does not support the act of self-reflection per se, but its precise function in self-processing remains unclear. In this article, I examine the hypothesis that the vMPFC may contribute to assign personal value or significance to self-related contents: stimuli and mental representations that refer or relate to the self tend to be assigned unique value or significance, and the function of the vMPFC may precisely be to evaluate or represent such significance. Although relatively few studies to date have directly tested this hypothesis, several lines of evidence converge to suggest that vMPFC activity during self-processing depends on the personal significance of self-related contents. First, increasing psychological distance from self-representations leads to decreased activation in the vMPFC. Second, the magnitude of vMPFC activation increases linearly with the personal importance attributed to self-representations. Third, the activity of the vMPFC is modulated by individual differences in the interest placed on self-reflection. Finally, the evidence shows that the vMPFC responds to outer aspects of self that have high personal value, such as possessions and close others. By assigning personal value to self-related contents, the vMPFC may play an important role in the construction, stabilization, and modification of self-representations, and ultimately in guiding our choices and decisions.